THE INFLUENCE OF PERSONAL BRANDING IN INCREASING SELF-VALUE AND BUSINESS CREDIBILITY - Rezkayanti, Rezkayanti; Sunusi, Seny Luhriyani; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research explores the strategies and techniques for building the personal branding of Muhammad Fadel Austyn Ramadhan and Nurannisa Taswin through their personal Instagram accounts. A qualitative approach with a case study was used, using instruments such as checklists, documentation, and literature to evaluate the 8 elements of building personal branding according to Montoya. The results show that both have successfully built strong personal branding, encompassing specialization, leadership, personality, and distinctiveness and highlight the role of speculation in enhancing self-value and credibility on social media.